2021
DOI: 10.31681/jetol.922682
|View full text |Cite
|
Sign up to set email alerts
|

Trend of distance education research in the covid-19 period: A bibliometric and content analysis

Abstract: The study aims to reveal the studies' profile for distance education activities in the Covid-19 period. For this purpose, bibliometric analysis and content analysis were used together in the study. Within the scope of the study, 220 studies were selected in the Web of Science database to access the articles. Within the scope of bibliometric analysis, the most used keywords, the most cited journals, the most publishing journals, the most publishing countries and the most cited authors were analyzed with the VOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
6
22
0
Order By: Relevance
“…Since education has a significant impact on a country's development (Petrakis & Stamakis, 2002), competitiveness (Lachmann, 1999), and socio-economic development (Sakmurzaeva, 2018), the collected results are acceptable. The findings regarding the keyword analysis within the scope of the research were similar to the keywords in the studies conducted by Yavuz et al (2021), Karakose & Demirkol (2021), Erbay (2020), andSweileh (2021).…”
Section: Co-occurrence Analysissupporting
confidence: 74%
See 4 more Smart Citations
“…Since education has a significant impact on a country's development (Petrakis & Stamakis, 2002), competitiveness (Lachmann, 1999), and socio-economic development (Sakmurzaeva, 2018), the collected results are acceptable. The findings regarding the keyword analysis within the scope of the research were similar to the keywords in the studies conducted by Yavuz et al (2021), Karakose & Demirkol (2021), Erbay (2020), andSweileh (2021).…”
Section: Co-occurrence Analysissupporting
confidence: 74%
“…Considering that the COVID-19 epidemic started in December 2019 and the subsequent transition to distance education, this situation can be interpreted as an expected result. Yavuz et al (2021) examined the articles about distance education during the pandemic and concluded that the studies were mainly published in the last quarter of 2020. Sweileh (2021) stated that publications on distance education in the field of health reached a peak in 2020.…”
Section: Distribution Of Articles By Yearmentioning
confidence: 99%
See 3 more Smart Citations